Impact of Budget Deficit on Inflation: A Case Study of Pakistan - Hamza, Muhammad; Bhatti, Muhammad Azhar; Kiran, Kokab (iRASD Journal of Economics, 2019)
The research is concerned with examining the effect of budget deficit on inflation a case of Pakistan economy. As inflation is one of the most prominent macro-economic indicator which tells us about how the prices in country are reacting and subsequently how other factors are being affected. So in this study we have analyzed the effect of budget deficit on inflation. As Pakistan is a developing nation where inflation and budget deficit are two major issues so for that reason we included the effect of budget deficit. The dependent variable is inflation and independent variables are money supply, GDP growth, unemployment, official exchange rate and fiscal deficit. The data is from 1985 to 2017. For checking unit root we applied augmented dickey fuller test and the study applied the Auto Regressive Distributed Lag Model (ARDL) method. The data is taken from world development indicator and from Pakistan Economic Survey. The results conclude that budget deficit, GDP growth and money supply have positive impact while unemployment and official exchange rate have negative impact. The study suggests that the government should focus on generating new revenue sources rather the foreign financing.